Prūsų kalbos linksniavimo sistema ir jos kitimas - Kaukienė, Audronė (Baltistica, 1995)
THE DECLENSION OF OLD PRUSSIAN AND IT’S EVOLUTION There are two dialects we can reconstruct in old Prussian, which differ territorially and chronologically. They also have different declension and stem-system. We can reconstruct quite ancient paradigm with all Baltic stems and three gender forms in the dialect of Elbing vocabulary (look at the table in 1.). The declension system of the dialect of Catechisms performed as the result of many phonetic changes (the widening of short vocals i, u, the narrowing of long vocal ē and especially the changing ā>ū after the labial and guttural consonants and the strong flexion shortening). That is why the mixing of the stems has started. The features of stem survived best in Nominative forms (2.1.). In other cases formed two types of declension: hard (with vocal a dominating in the flexion) and soft (with the vocals i (e) dominating in the flexion) (2.2.1.–2.2.4.). Beside the opposition a || i raised a new one u || i (2.3.–2.3.4.). The evolution of old Prussian declension system could be explained by the inherent laws of the language itself, not searching for the influence of other languages.